2017
DOI: 10.3389/fpls.2017.01247
|View full text |Cite
|
Sign up to set email alerts
|

Rosaceae Fruit Development, Ripening and Post-harvest: An Epigenetic Perspective

Abstract: Rosaceae is a family with an extraordinary spectrum of fruit types, including fleshy peach, apple, and strawberry that provide unique contributions to a healthy diet for consumers, and represent an excellent model for studying fruit patterning and development. In recent years, many efforts have been made to unravel regulatory mechanism underlying the hormonal, transcriptomic, proteomic and metabolomic changes occurring during Rosaceae fruit development. More recently, several studies on fleshy (tomato) and dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 153 publications
2
34
0
Order By: Relevance
“…The main actors (TF) involved in the transition from fruit growth to ripening have been identified ( Giovannoni, 2007 ), and epigenetic regulation of the targets of these master regulators has also been described in tomato ( Giovannoni et al., 2017 ). Regarding postharvest, epigenetic regulation of the senescence process has been explored in tomato, strawberry, and citrus ( Farinati et al., 2017 ). In comparison, in stone fruits information is scarce, but it is starting to emerge ( Fresnedo-Ramírez et al., 2017 ; Ma et al., 2018 ).…”
Section: Future Perspectives For Improving Type and Levels Of Secondamentioning
confidence: 99%
“…The main actors (TF) involved in the transition from fruit growth to ripening have been identified ( Giovannoni, 2007 ), and epigenetic regulation of the targets of these master regulators has also been described in tomato ( Giovannoni et al., 2017 ). Regarding postharvest, epigenetic regulation of the senescence process has been explored in tomato, strawberry, and citrus ( Farinati et al., 2017 ). In comparison, in stone fruits information is scarce, but it is starting to emerge ( Fresnedo-Ramírez et al., 2017 ; Ma et al., 2018 ).…”
Section: Future Perspectives For Improving Type and Levels Of Secondamentioning
confidence: 99%
“…These results revealed that pear, peach, and strawberry fruits underwent extensive cell division before 42, 21, and 19 DAFB, respectively, then underwent cell enlargement. In addition, both the single and double sigmoid curve occurred after these days, we concluded that both single and double sigmoid patterns were a result of cell expansion, not cell division [1][2][3][4].…”
Section: Investigation Of Growth Curves In Pear Peach and Strawberrmentioning
confidence: 99%
“…Within the Rosaceae, different fleshy fruit types showed two different fruit growth patterns. Pome fruits such as apple and pear exhibit a single sigmoid pattern in which fruits undergo extensive cell division during the first few weeks immediately following fertilization, after which almost all growth is due to cell enlargement [1][2][3][4]. Stone fruits such as late-maturing peach exhibit a double sigmoid pattern in which two rapid-growth stages are separated by a slow-growth stage [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent independent studies, as well as reviews, have indicated that such modifications to the classical climacteric ripening implicate several pathways that operate concomitantly with ethylene biosynthesis and perception, including AOX respiration, signaling by reactive oxygen species (ROS), and pathways that may be triggered by changes in epigenetic signatures (Perotti et al, 2014;Kumar et al, 2016;Farinati et al, 2017;Bucher et al, 2018;Hendrickson et al, 2019;Hewitt et al, 2020b). New advances in genome editing have provided further insight regarding potential sites for variation in ripening, as manipulation of upstream transcriptional regulators (Ito et al, 2017) leads to alterations in fruit texture, photoperiodic response, and posttranscriptional regulation of ripening-related genetic elements (Martín-Pizarro and Posé, 2018).…”
Section: Reexamining the Classical Model For Ethylene-dependent Ripeningmentioning
confidence: 99%